Heat, salt, and volume transports in the eastern Eurasian Basin of the Arctic Ocean from 2 years of mooring observations - A. V. Pnyushkov; I. V. Polyakov; R. Rember; V. V. Ivanov; V. V. Ivanov; M. B. Alkire; I. M. Ashik; T. M. Baumann; G. V. Alekseev; A. Sundfjord (Ocean Science, 2018)
This study discusses along-slope volume, heat, and salt transports derived from observations collected in 2013–2015 using a cross-slope array of six moorings ranging from 250 to 3900 m in the eastern Eurasian Basin (EB) of the Arctic Ocean. These observations demonstrate that in the upper 780 m layer, the along-slope boundary current advected, on average, 5.1±0.1 Sv of water, predominantly in the eastward (shallow-to-right) direction. Monthly net volume transports across the Laptev Sea slope vary widely, from ∼ 0.3±0.8 in April 2014 to  ∼ 9.9±0.8 Sv in June 2014; 3.1±0.1 Sv (or 60 %) of the net transport was associated with warm and salty intermediate-depth Atlantic Water (AW). Calculated heat transport for 2013–2015 (relative to −1.8 °C) was 46.0±1.7 TW, and net salt transport (relative to zero salinity) was 172±6 Mkg s−1. Estimates for AW heat and salt transports were 32.7±1.3 TW (71 % of net heat transport) and 112±4 Mkg s−1 (65 % of net salt transport). The variability of currents explains ∼ 90 % of the variability in the heat and salt transports. The remaining  ∼ 10 % is controlled by temperature and salinity anomalies together with the temporal variability of the AW layer thickness. The annual mean volume transports decreased by 25 % from 5.8±0.2 Sv in 2013–2014 to 4.4±0.2 Sv in 2014–2015, suggesting that changes in the transports at interannual and longer timescales in the eastern EB may be significant.